RECIPROCAL TEACHING: ONE OF THE METHODS FOR POOR COMPREHENDERS - Yawisah, Umi (Department of English Education of STAIN Jurai Siwo Metro, 2013)
Abstract : Reciprocal teaching is aÂ methodÂ which emphasizesÂ the studentsâ cognitive and meta cognitiveÂ domains for it covers the structural process of the instruction. TheÂ whole elements within the procedure enable the students toÂ choose the strategy, plan, monitor, and evaluate their ownÂ activities. Furthermore, the procedures integrated in this method Â are believed toÂ enhance the studentsâ thinking process. The method, introduced byÂ Palinscar and Brown, belongs to cooperative learning in that the studentsâ thinking process in learning is expressed through a natural dialogue. This method is designed to improve the studentsâ competency in text reading while those students find it difficult to comprehend the content of the text. The method also encourages the students to apply such four strategies as predicting, summarizing, questioning, and clarifying.Â Key words: reciprocal teaching, method, reading, thinking process